Research on Rural Development Pathways Driven by External Projects: A Case Study of Village S - Qin Zou (International Journal of Social Sciences and Public Administration, 2026)
Against the backdrop of China's rural revitalization strategy, attracting external capital through project recruitment has become a common model for promoting rural industrial development. Taking Village S in City N, Province S as a case study, this paper analyzes the process of integrating government-led external capital, technology, and local rural resources. The study finds that Village S achieved short-term industrial upgrading and increased farmers' incomes through mechanisms such as "government bridging, resource coupling, contractual integration, and limited spillover." However, problems also emerged, including low levels of farmer participation, weak benefit-linking mechanisms, and insufficient endogenous momentum. The research shows that while the project recruitment model yields quick results, it also faces sustainability challenges. In the future, alongside project introduction, greater attention should be paid to safeguarding farmers' principal status, improving benefit distribution mechanisms, and enhancing villages' self-development capacity, so as to achieve the transition from "external blood transfusion" to "internal hematopoiesis."